Bridging the gap: exploring the influence of human capital factors on job matching in Malaysia / Low Choon-Wei and Mah Pei-Yew - Low, Choon-Wei; Mah, Pei-Yew (2023)
Job mismatch is an issue that brings negative impacts on economic growth. It happens in developing and developed countries. This study focuses on the Malaysian context. There was an expansion in the labor market and education sector in Malaysia. With more labor force entering the labor market, the number of employed persons has increased. However, the underemployment rate was increasing in Malaysia, registered at 37.4% in the fourth quarter of 2022. This study examines how human capital factors link to the happening of job mismatch. This study involves 347 Malaysian employees in a questionnaire survey. We use a logistic regression model to analyze the collected responses. Hence, this study provides empirical evidence on job matching of Malaysian employees and investigates the likelihood of job mismatch due to human capital factors including working experience, and education attainment. Findings show that working experience and education attainment are negatively associated with job mismatch and can significantly influence job-matching outcomes. The current study provides essential practical implications. The findings revealed that human capital factors including working experience and educational attainment are important for individuals to remain relevant in the job market. These results point to the importance of employers protecting the well-being of their employers such as rewards and benefits, recognitions, promotion opportunities, and work-life balance to enhance job satisfaction, and hence, retain them in the organization.